Sample teaching modules on selected units of third year communication arts (English) - Abello, Wilhelmina Lucie Battung 1930-
This study gives sample teaching modules on Units I and II of Third Year Communication Arts (English). The writer used literary pieces which offer ample opportunities for the enhancement of basic and related skills along the four communication avenues of listening, speaking, reading and writing coupled with concepts and values relevant to adolescents and adolescent life.